2014
DOI: 10.7763/jocet.2014.v2.114
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Design in Event Design: Opportunities and Limitations

Abstract: Abstract-Events offer valuable economic, social, cultural and educational benefits, and potential growth in tourism for many international destinations. As society gains a greater understanding about these impacts, events are being challenged to become more accountable for their managerial decisions and to produce outcomes which are more sustainable on multiple criteria and have positive environmental impacts. The purpose of this study was to discuss sustainable design in event design. Literature review will b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 11 publications
0
4
0
4
Order By: Relevance
“…However, on this note, festivals are often deemed threats to the natural environment as they draw a large number of attendees to a specific space and time while utilizing resources (Zifkos, 2015). The event industry is compelled to be more responsible in its managerial decisions and create positive environmental impacts (Mokhtar, Deng, 2014). In their work, Yamagishi, Gantalao and Ocampo (2022) found that most festival organizations, at least in their conditions, have a myopic green management agenda denying salient environmental threats linked to managing festivals.…”
Section: Towards the Green Management Of Eventsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, on this note, festivals are often deemed threats to the natural environment as they draw a large number of attendees to a specific space and time while utilizing resources (Zifkos, 2015). The event industry is compelled to be more responsible in its managerial decisions and create positive environmental impacts (Mokhtar, Deng, 2014). In their work, Yamagishi, Gantalao and Ocampo (2022) found that most festival organizations, at least in their conditions, have a myopic green management agenda denying salient environmental threats linked to managing festivals.…”
Section: Towards the Green Management Of Eventsmentioning
confidence: 99%
“…The event industry is compelled to be more responsible for creating positive environmental impacts (Mokhtar, Deng, 2014) and in the event industry, stakeholders are increasingly interested in adopting green initiatives to enhance competitiveness (Mankaa et al, 2018;Whitfield, Dioko, 2012). Green events incorporate sustainable measures and practices in their management and operations (Laing, Frost, 2010;Martinho et al, 2018;UNEP, 2009).…”
Section: Towards the Green Management Of Eventsmentioning
confidence: 99%
See 3 more Smart Citations